Cerebral venous sinus thrombosis as the initial presentation of systemic lupus erythematosus. (February 2020) - Chandra, T; Tilstra, J S
Systemic lupus erythematosus (SLE) is a hypercoagulable state due to a variety of mechanisms. Herein, we discuss the case of a 40-year-old gentleman who presented with cerebral venous sinus thrombosis (CVST) as the first manifestation of underlying SLE. On initial presentation, he did not endorse any other signs and symptoms to suggest the presence of an autoimmune condition. Work-up revealed an absence of antiphospholipid antibodies. Further evaluation uncovered the underlying etiology of the CVST as SLE-induced nephrotic syndrome. The existing literature on CVST suggests that there are only two other biopsy-proven cases of lupus nephritis leading to nephrotic range proteinuria as the etiology for CVST. Given the rarity of this presentation, there are no clearly delineated treatment strategies.